Limnology and fisheries of Doyang reservoir inNagaland, India - Haldar, R S; Vass, K K; Raina, H S (Indian Journal of Fisheries, 2011)
The paper embodies the recent limnological and fisheries investigations madeonÂ Doyang reservoir in Nagaland, to propose an effective fishery management.The impoundment was constructed in July 2000 across the river Doyang andstill in the process of getting stabilized. During the investigation no thermal oroxygen stratification was recorded.Â In the reservoir, fishery exploitation is aimedat the larger fishes, primarily Cyprinids, while other fish species are small insize and of less economical value, but are significant from biodiversity viewpoint.The experimental fishing in the reservoir revealed main contribution of Cyprinuscarpio var.Â communis, Catla catla, Labeo dero and Tor putitora in the order oftheir dominance. Majority of these species must be sustaining as self-recruits.Some approaches for reservoir fisheries management have been proposed.